A novel Z-scheme BiPO4-Bi2O2(OH)(NO3) heterojunction structured hybrid for synergistic photocatalysis. (March 2017) - Liu, Guoshuai; You, Shijie; Huang, Hong; Ma, Ming; Ren, Nanqi
Abstract: Photocatalysis has been gaining a growing popularity in water treatment, and their engineered applications inspire the development of effective photocatalyst materials. To develop photocatalyst that is effective for degradation of organic pollutants, we fabricate a novel direct solid Z-scheme BiPO4 -Bi2 O2 (OH)(NO3 ) (BPO-BHN) heterojunction structured hybrid. The results demonstrate an enhanced photocatalytic activity of BPO-BHN to produce OH radicals, according to diffuse reflectance spectroscopy (DRS), electron spin-resonance resonance (ESR), photoelectrochemical measurements, and theoretical calculation results. The BPO-BHN is shown to greatly promote the degradation of 2, 4-dichlorophenol (2, 4-DCP) under ultraviolet light. On the basis of pseudo-first-order kinetics, the apparent degradation rate constant ( k app ) of 0.050 min −1 obtained for BPO-BHN is approximately 3.33 and 12.5 times of that for individual BPO ( k app  = 0.015 min −1 ) and BHN ( k app  = 0.004 min −1 ), respectively. This suggests a virtually synergistic photocatalysis of BPO and BHN when they form a direct solid Z-scheme heterojunction structure, which is favorable for improving UV-light harvesting, hole/electron separation and oxidizing capability. In particular, as a novel non-linear optical (NLO) material, the BHN plays a significant role in the formation of Z-scheme structure for its unique ability of capturing photo-electrons from BPO by high-potential C + face in valence band. This study provides a proof-of-concept strategy to develop more effective photocatalysts for degradation of organic pollutants in water. Graphical abstract: Highlights: A novel direct solid Z-scheme BPO-BHN heterojunction structured hybrid is fabricated. Synergistic photocatalysis improves light harvesting, hole/electron separation and oxidizing capability. The BPO-BHN hybrid achieves effective degradation of 2, 4-DCP.